PENCEGAHAN TIMBULNYA DORK PADA SEARCH ENGINE GOOGLE DENGAN PLUGIN - Ibrahim Risyad; Dina Maulinaq (Jurnal Mantik Penusa, 2016)
In a google search engine there is a feature called google dork query or often called a dork. This feature is used for advanced searches using search operators provided by google to find information that should not be visible on the website but indexed and can be seen on google search engine. This feature is often used to find security holes by hackers so the hackers can easily read on a website file structure for later exploitation. Therefore needs to be made a plugin or tool to prevent dork in a google search engine. How this plugin works is to add a html attribute such as meta tag which will tell the Google's robot crawlers to not crawling unwanted web pages appear on search engines.